Rancang Bangun Aplikasi Pakar Untuk Mendiagnosa Kerusakan Pada Mobil Jenis MPV Menggunakan Metode Forward Chaining dan Certainty Factor - Alamsyah, Hadi; Nuraeni, Fitri (Institut Teknologi Garut, 2025)
One of the most widely used vehicles today is the car. Over time the car will experience damage, which to find out the damage that occurs requires an expert. This research aims to develop a web-based expert application that is able to diagnose damage to MPV type cars using the forward chaining method and certainty factor. The forward chaining method is used to perform rule-based inference from symptoms to conclusions, while the certainty factor is used to calculate the certainty level of diagnosis. The system was developed using the expert system development life cycle methodology which includes assessment, knowledge acquisition, design, test, documentation, and maintenance stages. The results show that this expert application can diagnose 16 types of damage with an accuracy rate of 90%. The main contribution of this research is the development of an expert system application that can be accessed by the wider community to assist in diagnosing vehicle damage independently, so as to save time and repair costs.